Technology for dementia care: benefits, opportunities and concerns - Yesoda Bhargava; Veeky Baths (Inishmore Laser Scientific Publishing Ltd, 2022)
The rise in incidence and prevalence of dementia globally is driving the technological revolution to develop effective healthcare solutions for dementia patients and caretakers. These solutions promise enhanced mechanisms to manage lifestyle, monitor cognitive performance, ensure the security and safety of the elderly, and deliver rehabilitation services. In this viewpoint, we contextualize the role of technology in dementia care by elaborating on these solutions and discussing the associated benefits, opportunities, and concerns.